Bagian Depan Vol.24 No. 1 (2022): February 2022 - Editor in Chief (JURNAL TEKNOLOGI REAKTOR NUKLIR TRI DASA MEGA, 2022)
This section consists of Cover Page, Editorial Board Page, Peer Reviewer Page, Table of Content Page and Preface Page